The Utilization of the Mappadendang Ritual as a Local Wisdom Based Learning Resource: Penelitian - Ita Rosvita; Filawati; Andi Fatimah Yunus (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aimed to describe the local wisdom values embedded in the Mappadendang ritual and to examine its potential as a local wisdom-based learning resource. The study employed a qualitative approach with a descriptive design and was conducted from April to May 2026 in Jampuserengnge Village, Liliriaja District, Soppeng Regency, South Sulawesi, Indonesia. Data were collected through observation, in-depth interviews, and documentation involving traditional leaders, community leaders, and local community members who participated in the implementation of the Mappadendang ritual. Data trustworthiness was ensured through source and technique triangulation, while data were analyzed using the interactive model proposed by Miles, Huberman, and Saldaña, consisting of data reduction, data display, and conclusion drawing. The findings revealed that the Mappadendang ritual embodies various local wisdom values, including mutual cooperation, togetherness and social solidarity, religiosity, cultural preservation, and environmental awareness. These values are reflected throughout every stage of the ritual, which involves active, collective, and sustainable community participation. Furthermore, the study found that Mappadendang has considerable potential to be utilized as a learning resource in Indonesian Language, Pancasila Education, Social Studies, and Arts Education. The integration of this ritual into learning activities can create more contextual, meaningful, and culturally relevant learning experiences for students.